A Growing Fire Hazard Concern in Communities: Home Oxygen Therapy and Continued Smoking Habits. (February 2015) - Galligan, Catherine J.; Markkanen, Pia K.; Fantasia, Linda M.; Gore, Rebecca J.; Sama, Susan R.; Quinn, Margaret M.
The Safe Home Care Project investigated both qualitatively and quantitatively a range of occupational safety and health hazards, as well as injury and illness prevention practices, among home care aides in Massachusetts. This article reports on a hazard identified by aides during the study's initial focus groups: smoking by home care clients on long-term oxygen therapy. Following the qualitative phase we conducted a cross-sectional survey among 1, 249 aides and found that medical oxygen was present in 9 percent of aide visits (314 of aides' 3, 484 recent client visits) and that 25 percent of clients on oxygen therapy were described as smokers. Based on our findings, the Board of Health in a local town conducted a pilot study to address fire hazards related to medical oxygen. Medical oxygen combined with smoking or other sources of ignition is a serious fire and explosion hazard that threatens not only workers who visit homes but also communities.